Interactive PAI Science Quiz to Increase Students' Competitive Power through Kodular Applications: Kuis Interaktif Ilmu PAI untuk Meningkatkan Daya Kompetitif Siswa melalui Aplikasi Kodular - Salsabila, Unik Hanifah; Nashrul Mu'minin, Nashrul; Zuhdi, Mohammad Naufal; Maulana, Ikhwan Tegar; Ginajar, Muhammad (PT. Alpha Trianguli Australis, 2024)
This research aims to increase student involvement in Islamic Religious Education (PAI) subjects by utilizing a mobile learning application equipped with an interactive quiz feature built using the Kodular platform. The basis of this research was inspired by the results of previous research which showed that the use of technology can be effective in increasing students' motivation and level of participation in the PAI learning process. In order to achieve this goal, this research adopts a research and development (R&D) approach to design and implement a PAI interactive quiz application that utilizes the Kodular platform. The application is aimed at junior high school (SMP) students. In the development stage, the research team designed and developed the PAI interactive quiz application using the Kodular platform which allows creating mobile applications visually without requiring complex programming. This application is equipped with an interactive quiz feature that supports PAI learning. The result of this research is a Kodular-based learning media application. In conclusion, the integration of mobile learning technology offers an interactive, flexible and interesting learning experience for students, which contributes to increasing student motivation and participation in PAI learning. This research contributes to the development of innovative and effective PAI teaching methods through the use of technology.